Oral Administration of 5-Hydroxytryptophan Restores Gut Microbiota Dysbiosis in a Mouse Model of Depression - Wu, Lijuan; Ran, Lisha; Wu, Yazeng; Liang, Manyu; Zeng, Jing; Ke, Famin; Wang, Fang; Yang, Jian; Lao, Xiaoqing; Liu, Li; Wang, Qin; Gao, Xiaowei (Frontiers in Microbiology, 2022)
5-Hydroxytryptophan (5-HTP) has positive clinical effects on various neuropsychiatric and metabiotic disorders, especially depression. Although it increases serotonin levels in the brain and gastrointestinal tract, its pharmacology remains largely unknown. Our goal was to determine the effects of 5-HTP on the mouse gut microbiome, which has a close relationship with depression through the “microbiota-gut-brain axis.” We confirmed that depressive disorder restructures the gut microbial community, and 5-HTP efficiently improves depressive symptoms in mice. Oral administration of 5-HTP significantly restored gut microbiota dysbiosis in mice with depression-like behaviors. The diversity and richness of gut microbial communities and relative abundance of specific microbial taxa at both phylum and genus levels were partially recovered. 5-HTP exhibited some positive effects on restoring the alterations in the concentrations of short-chain fatty acids and brain-derived neurotrophic factors caused by depression in mice. Our results may provide new insights into the pharmacology of 5-HTP in treating depression and other disorders.